Validation of an immersive virtual reality device accepted by seniors that preserves the adaptive behavior produced in the real world - Delbes, Lisa; Mascret, Nicolas; Goulon, Cédric; Montagne, Gilles (Frontiers in Bioengineering and Biotechnology, 2022)
Falls in the elderly are a major societal issue. Virtual Reality (VR) appears as a relevant tool to propose gait training programs to prevent the occurrence of falls. The use of a head-mounted device (HMD) allows overground walking during fully immersive virtual training sessions. Our long-term ambition is to develop gait training programs with an HMD to propose enjoyable and personalized training content for the elderly. Before proposing these programs, several methodological precautions must be taken. The first concerns the supposed similarity of the adaptive behavior produced in the real world and in virtual reality. The second concerns the acceptance of the VR device (HMD) before and after use. Twenty older adults performed a locomotor pointing task in three conditions including a real-world condition, a virtual-world condition consisting in a replica of the real-world condition, and a virtual condition in which the locomotor point task was performed in a different context. From feet positions in relation to the position of a target, gait adaptability behavior was investigated. In line with previous studies, step adjustments (needed and produced) were investigated through a combination of inter-trial and trial-by-trial analyses. The results highlighted that participants adopted the same gait adaptability behavior whatever the type of environment (real vs virtual). Gait analyses suggested the use of a generic control mechanism based on information-movement coupling. We also demonstrated that older adults accepted the VR device before and after use. With these methodological locks removed, it is now possible to design training programs in virtual reality to prevent falls in the elderly.